Resilience in Patients With Recent Diagnosis of a Schizophrenia Spectrum Disorder. Issue 8 (August 2016) - Bozikas, Vasilis P.; Parlapani, Eleni; Holeva, Vasiliki; Skemperi, Eleni; Bargiota, Stavroula I.; Kirla, Danai; Rera, Eirini; Garyfallos, Georgios
Abstract : Abstract: This study focused on resilience in patients who recently received a diagnosis of schizophrenia spectrum disorder (SSD). Psychopathological symptoms, depressive symptoms, and hopelessness were considered as sources of stress in the context of psychosis. Forty-eight SSD patients (mean period between diagnosis and recruitment, 20.79 months) were enrolled. Psychopathological symptoms were assessed by the Positive and Negative Syndrome Scale, depression by the Calgary Depression Scale for Schizophrenia, hopelessness by the Beck Hopelessness Scale, and functioning by the Social and Occupational Functioning Scale. Resilience was evaluated by the Connor-Davidson Resilience Scale, which was additionally completed by 81 healthy controls. Patients demonstrated less resilience than did healthy participants. Female patients showed higher resilience levels and functioning than did males. High resilience levels were associated with less severe positive symptoms, general psychopathological symptoms, depression, and hopelessness. Apart from negative symptoms, results indicated that resilience may be a potential moderator of functioning. Thus, resilience-oriented interventions might constitute an additional therapeutic approach for SSD patients.